The lost journal of Alejandro Pardo meet the dark creatures from Philippines mythology - Hontiveros, Dave; Tan, Budjette; Baldisimo, Kajo 1978-; Guerrero, Johannes Ma. C.; Malonzo, Mervin; Camara, Frank (Tokyo Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2022)
"A fascinating field guide to Philippine monsters and mythology! From award-winning authors Budgette Tan and David Hontiveros comes The Lost Journal of Alejandro Pardo --a 19th-century cryptozoologist's account of his encounters with the strange and magical creatures from Philippine legends and mythology. In this book, you'll come face-to-face with 36 mythical beasts including: The Kapre --A shape-shifter that morphs before your very eyes, disguising itself as what you think is your dog or your mom! The Mangalok --An angel-faced predator who feasts on human flesh! The Pugot --A headless beast aptly described as a "living, breathing volcano"! And many more! Pardo describes 36 fantastical animals in total, highlighting his encyclopedic knowledge of the unique creatures found in all parts of the Philippines (which is undeniable, even if he is a bit of a lout). Pardo's lost journal is full of eye-witness details of his exciting travels in search of mythical beings. Don't miss out on his extraordinary adventures!"--Provided by publisher.
"Published in the Philippines by Summit Publishing, 2015"--Page facing title page.
Keywords: Animals, Mythical -- Philippines -- Comic books, strips, etc; Folklore -- Philippines -- Comic books, strips, etc; Mythology, Philippine -- Comic books, strips, etc